IMPLEMENTASI CASH MANAGEMENT MODEL (Kasus Pada Direktorat Jenderal Perbendaharaan, Kementerian Keuangan RI) - , Catur Rini Ariyanti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to examine and find a method that is considered most appropriate for government financial management by determining the optimal level of cash balances to be maintained as cash reserves in case of sudden cash disbursements or cash receipts failure. Cash management model used in this study, the simple cash balance, models of Allais-Baumol-Tobin (BAT) and Miller-Orr model. This study uses daily data of government cash flows and also data issuance of Government Securities. This data be used for determining the target cash balance, opportunity cost, trading cost, total cost and also the total benefits derived from each model. The result showed the lowest opportunity cost resulting from the Miller-Orr model of Rp.1.398.247.667.994,78, the highest trading costs by Miller- Orr model of Rp.13.536.533.030.107,10 and also the largest total benefit obtained from this model Rp.6.010.117.328.258.770. If the comparison between model BAT with the Miller-Orr model, the Miller- Orr model is better because with a lower cash balance can obtain greater benefits, but when compared with the simple cash balance, then the simple cash balance is better than Miller-Orr model because the trading cost difference between this model is much larger when compared with its opportunity cost difference, amounting to Rp.12.122.851.447.280,92 for the trading costs and Rp.11.990.499.820.844, 02 for opportunity cost.